PENERAPAN STRATEGI REMOTE LEARNING PADA PEMBELAJARAN PAI DALAM MENGATASI KESULITAN BELAJAR SISWA MASA PANDEMI COVID-19 DI SMP NEGERI 1 KEPANJEN - Moch Adib Nasrulloh; Jazari Jazari; Muhammad Fahmi Hidayatullah (VICRATINA, 2021)
The application of remote learning strategies can be a teacher's solution in overcoming student learning difficulties. Especially during a pandemic like today, a solution is needed so that learning continues even though it is remote. The implementation of this strategy is a challenge for Islamic religious education teachers at SMP Negeri 1 Kepanjen. The existence of a remote learning strategy is expected to be able to overcome student’s learning difficulties in learning Islamic religious education. The focus of the research discusses the implementation, planning and evaluation of remote learning strategies. To achieve this goal, the researcher used a qualitative descriptive approach and the type of research used was a case study. Researchers found the results of this study include planning, implementing, and evaluating remote learning strategies. Remote learning strategy planning in PAI learning preparation of steps for using media such as whatsapp and google form. The application uses the whatsapp application and google form. The evaluation is seen from the ability and student learning outcomes.